Faktor yang Berhubungan dengan Penggunaan Alat Pelindung Diri secara Lengkap pada Bidan (Studi di Wilayah Kerja Kabupaten Bondowoso) (Determinant of Complete Personal Protective Equipment Using for Midwives (study in Work Region of Bondowoso District) - Shofiyah Vita Yuliana; Ragil Ismi Hartanti; Irma Prasetyowati (UPT Percetakan dan Penerbitan Universitas Jember, 2016)
Midwives have to wear PPE completely, such as head cover, goggles, mask, gloves, apron, andboots. But not all of them using PPE completely for 75% in Bondowoso. This study aims was toanalyze the factors related to completely using of PPE for midwives in work region of Bondowoso.This study held in Mey 2015-February 2016. This study used cross sectional approachment. Thepopulations of this study were 116 Delima midwives in Bondowoso. The result showed that themidwives’s knowledge was in the medium level, most were positive attitude, they had sameeducation level (between D3-D4), their age were about 35-44 years old, and most of them hadbeen working for 21-30 years. The midwives wore PPE completely in I stage (2,8), II and III stage(11,1) and all of them did not wear PPE completely in IV stage.There was significant correlation ofattitude to complete PPE using for midwives in I stage and no significant correlation of knowledge,attitude, education, age, work stage to complete PPE using for midwives of II and III stage inBondowoso. There was no significant correlation between the PPE availability with complete PPEusing for midwives in I stage and significant correlation between the PPE availability with completePPE using for midwives of II and III stage in Bondowoso. There was no significant correlationbetween training and monitoring with complete PPE using for midwives of I, II, III stage inBondowoso.Keywords: factors individual , PPE availability, training and monitoring factor.